Análisis de producción de metano a partir del desarrollo de un generador de energía no contaminante (2021)
The production of renewable, affordable and non-polluting energy can be carried out through the management of organic waste found in everyday life, this process called anaerobic digestion, is a popular technology implemented and researched in laboratories in many countries through of the world. The raw data collected in laboratory experiments indicate quantities and rates of methane (CH4) production, this requires a sequence of conceptually simple calculations but great dedication with respect to time since most publications do not explain in detail its process and many times these types of calculations become a bit tedious. For all this, it is possible that the results obtained are not reproducible both in laboratories and in experiments, the implementation of biogas packages and programs allows us to address these types of problems and make predictions regarding the production of this biogas and then carry it out through face-to-face practice